Thieme Chemistry Journals Awardees – Where Are They Now?Carbene Organocatalysis for Stetter, Benzoin, Domino, and Ring-Expansion Reactions - Haghshenas, Pouyan; Langdon, Steven M.; Gravel, Michel (Synlett, 2017)
N-Heterocyclic carbene catalysis allows the rapid formation of functionalized carbon–carbon bonds. Our group has spent the previous decade focusing on broadening practical applications of this type of catalysis. The design and discovery of novel reactivities and catalysts in our group can best be divided into work focusing on the Stetter, ring-expansion, and cross-benzoin reactions. Along with our expansion of the reaction scope, our introduction of novel bis(amino)cyclopropenylidene catalysts for the Stetter reaction successfully suppresses formation of side products, increasing synthetic utility. Concurrent work on ring-expansion reactions allows access to functionalized lactones and lactams. In addition to expanding the scope of the cross-benzoin reaction through use of α-ketoesters and α-amino aldehydes, the introduction of a new triazolylidene catalyst has allowed access to general chemoselective cross-benzoin reactions between aliphatic and aromatic aldehydes.1 Introduction2 Stetter Reactions2.1 Domino Stetter Reactions3 Ring-Expansion Reactions4 Cross-Benzoin Reactions5 Summary and Outlook
Keywords: N-heterocyclic carbenes; organocatalysis; Stetter reaction; benzoin; enantioselective catalysis; ring expansion; cross-benzoin reaction